Health monitoring system using pulse oximeter with remote alert - Khalifa, Othman Omran (2015)
This A remote patient monitoring system is implemented which is used for real time monitoring of various heath parameters of a remotely based patient. Oxygen saturation and body temperature are the two parameters calculated and transmitted via a server to a remote client. The main purpose of this paper is to present a remote Pulse Oximetry System for health monitoring purposes. The framework lays on the idea that the vital health signs, can be collected from the patient and passed to a processer, where these signs will be processed, compared and monitored in order to alert important personnel in the case of an emergency. The blood oxygen saturation is the biometric sign which is monitored by this device .The technique used in this work is called “Photoplethysmography” which is based on the change in the intensity of light transmitted through the tissue due to arterial blood pulse. This technique converts the intensity of light into a voltage signal which is used to calculate the oxygen saturation of the patient. This is due to the fact that oxygenated blood has such characteristics in absorbing the Red and Infrared wavelengths which differs from the deoxygenated blood. Comparison of the two absorptions produces an estimation of the oxygen saturation in the patient’s blood.